Load and wear experiments on the impact hammer of a vertical shaft impact crusher. Issue 1 (November 2015) - Yang, J H; Fang, H Y; Luo, M
Abstract: Impact hammers are important components of impact crushers, and are often shortlived due to the high-impact nature of their use. Wear-resistant alloys are welded to the surface of impact hammers to prolong their service life. In this paper, a simulation model of the rotor and impact hammers in impact crushers was designed to utilize the Discrete Element Method (DEM). The wear-resistant alloy on each impact hammer was divided into twenty-two action regions. The load distribution on each alloy block is affected by the structural and manufacturing parameters of the impact crusher. The wear distribution of the impact hammer was measured by shape morphology according to relative impact crushers. The results demonstrated that the real measurements of wear distribution on the impact hammer were similar to simulated load distribution measurements on the same surface. The study of load distribution of impact hammers by DEM established a theoretical foundation on which to base the optimal design of impact crushers.